Management of Infrastructure Facilities in the Learning Process of Students (Case Study: MIN 1 Bener Meriah) - Mirela, Tiarani (Proceeding International Conference on Religion, Science and Education, 2022)
The more complete the facilities and infrastructure a school has, the easier it will be for teachers to carry out the learning process and the infrastructure is very much needed in the educational process. Like MIN 1 Bener Meriah, which has to implement a learning system alternately due to the lack of classrooms. The purpose of this study is to describe the management of educational facilities and infrastructure at MIN 1 Bener Meriah as an effort to maximize learning. This research is a qualitative type of data collection using observation, interviews, and documentation. And using data analysis using the Miles and Huberman model. Based on the findings of the management of educational facilities and infrastructure at MIN 1 Bener Meriah, namely: (1) Planning for educational infrastructure based on an analysis of the needs and number of APBS, (2) Procurement of educational facilities and infrastructure using purchases, grants / gifts from student guardians, and also submitting proposals to related parties. So that we can know if the complete facilities and infrastructure can be utilized properly, the learning process of students can run well.